Sovereign Debt Restructurings in Grenada: Causes, Processes, Outcomes, and Lessons Learned - Tamon Asonuma; Mike Xin Li; Michael G. Papaioannou; Saji Thomas; Eriko Togo (Journal of Banking and Financial Economics)
This paper documents the two debt restructurings that Grenada undertook in 2004–06 and 2013–15. Both restructurings emerged as a consequence of weak fiscal and debt situations, which became unsustainable soon after external shocks hit the island economy. The two restructurings provided liquidity relief, with the second one involving a principal haircut. However, the first restructuring was not able to secure long-term debt sustainability. Grenada’s restructuring experience shows the importance of (1) establishing appropriate debt restructuring objectives; (2) committing to policy reforms and maintaining ownership of the restructuring goals; and (3) engaging closely and having clear communications with creditors.